Seeing it first-hand: interpreters’ insights from working with LGBTIQA+ individuals settling in Australia - Lai, Miranda; Zhang, Epperly; Gonzalez, Erika (Frontiers in Communication, 2025)
This article uses the interpreter’s perspective to explore communication challenges arising from linguistic and cultural discordances faced by LGBTIQA+ migrants when accessing public services in Australia. Drawing on qualitative data collected through interviews with 24 interpreters working across 12 languages, this research reveals the multidimensional complexities of language mediation in encounters involving gender and sexual identity. The findings highlight three key challenges: (1) linguistic barriers, including the absence of standardised translated LGBTIQA+ terminology and difficulties with the use of pronouns; (2) cultural challenges, where interpreters need to strike a balance between linguistic accuracy and cultural sensitivity; and (3) the emotional burden borne by interpreters as a result of their exposure to sensitive, traumatic, or emotionally charged narratives. To address these issues, the study recommends developing multilingual LGBTIQA+ glossaries, improving interpreters’ access to briefings, and incorporating LGBTIQA+ topics into interpreter training and education. These measures aim to foster equitable, dignified communication for LGBTIQA+ migrants in Australia.